A human ex vivo atherosclerotic plaque model to study lesion biology - Erbel, Christian; Okuyucu, Deniz; Akhavanpoor, Mohammadreza; Zhao, Li; Wangler, Susanne; Hakimi, Maani; Dösch, Andreas; Dengler, Thomas; Katus, Hugo; Gleißner, Christian A. (JoVE. Science education, 2014)
Atherosclerosis is a chronic inflammatory disease of the vasculature. There are various methods to study the inflammatory compound in atherosclerotic lesions. Mouse models are an important tool to investigate inflammatory processes in atherogenesis, but these models suffer from the phenotypic and functional differences between the murine and human immune system. In vitro cell experiments are used to specifically evaluate cell type-dependent changes caused by a substance of interest, but culture-dependent variations and the inability to analyze the influence of specific molecules in the context of the inflammatory compound in atherosclerotic lesions limit the impact of the results. In addition, measuring levels of a molecule of interest in human blood helps to further investigate its clinical relevance, but this represents systemic and not local inflammation. Therefore, we here describe a plaque culture model to study human atherosclerotic lesion biology ex vivo. In short, fresh plaques are obtained from patients undergoing endarterectomy or coronary artery bypass grafting and stored in RPMI medium on ice until usage. The specimens are cut into small pieces followed by random distribution into a 48-well plate, containing RPMI medium in addition to a substance of interest such as cytokines or chemokines alone or in combination for defined periods of time. After incubation, the plaque pieces can be shock frozen for mRNA isolation, embedded in Paraffin or OCT for immunohistochemistry staining or smashed and lysed for western blotting. Furthermore, cells may be isolated from the plaque for flow cytometry analysis. In addition, supernatants can be collected for protein measurement by ELISA. In conclusion, the presented ex vivo model opens the possibility to further study inflammatory lesional biology, which may result in identification of novel disease mechanisms and therapeutic targets.